Automated Appliances using Microbit - Ahmad, Muhammad Shukri; K. Puspanathan,; T. Revi,; H. H. Tan, (Multidisciplinary Applied Research and Innovation, 2021)
The lamps and fans play an essential part in our daily lives. It makes our life more comfortable.We often need to get up from our seats to the switch,either to ON or OFF the electrical appliances,but forgetting to turn OFF the electrical appliances after using it will lead to wastage of electricity.The main objective of our project is to overcome these problems and make people’s life more comfortable especially for elderly people who have memory problems or for those who are immobilized.With this project,the electrical appliances,lights and fans will turn ON automatically when someone present and turn OFF automatically when they leave. This is achieved by using 2 type of sensors. Appliances can still be controlled using switches, but in addition it also can be controlled from smartphone by just sitting on chair. Mainly,the system consists of Microbit,to instruct the system properly and will automatically turn ON the fan when there is motion detected and turn OFF when there is no motion detected using Passive Infrared (PIR) Sensor. Furthermore, lamp will also turn OFF when the presence of light is detected (daytime) and turns ON when no presence of light is detected (night-time) by light dependent (LDR)sensor.Apart from that,the fan and lamp can be also controlled manually by using smartphone.Smartphone and the microbit are linked via Bluetooth connection.Therefore,by just installing‘micro:bit’ and ‘MIT A12 Companion’ applications from playstore,we would be able to control our electrical appliances at home easily without much effort.The goal of this final project is to make our lives more comfortable and easier and to move towards advanced technologies as modern technology has helped us in every sphere of life.